Management control systems and tools for internationalization success - Teixeira, Nuno Miguel, 1974- (Advances in human resources management and organizational development (AHRMOD) book series., 2020)
""This book examines internationalization processes and their costs, advantages and risks, and concepts, techniques and management control tools, and organizational performance evaluation instruments"--Provided by publisher"--